Action Research in Organizations Participation in Change Processes - Kristiansen, Marianne (Verlag Barbara Budrich, 2021)
Who decides to initiate change processes in organizations? Who sets the goals? What does it mean for employees to participate in change processes? The book examines organizational change processes based on collaboration between employers, employees and action researchers in Europe and the U.S. in the later part of the 20th century. The authors offer important insights into participation and change in organizations for researchers and practitioners by identifying dilemmas and paradoxes, conflicting interests and exercising of power.